Resilience Analysis of the Consensus Algorithm in Microgrids with Distributed Controllers Testing for Communication Link Failure - Silva, Paulo Fernando [UNESP]; Giacomini, Jairo [UNESP]; Bonaldo, Jakson Paulo; de Oro Arenas, Luis [UNESP]; de Arimatéia Filho, José O. [UNESP]; Paredes, Helmo Kelis Morales [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper addresses the growing interest in microgrid (MG) research, driven by the integration of renewable energy sources and the need for enhanced grid resilience and flexibility. The implementation of efficient and stable control systems is crucial for the optimization of MG operation. This study investigates the resilience of the consensus algorithm within an MG comprising three-phase four-wire generators under a distributed control system. The simulations explore various communication scenarios to assess the tolerance of the communication link under failures and their impact on MG stability. The results highlight that consensus algorithm maintain robustness and resilience even when communication links fail. These characteristics are essential for distributed control systems, where communication between generators can be interrupted or exposes to temporary failures. Consequently, effective power sharing in the MG can still be achieved, underscoring the efficacy of the algorithm in maintaining MG performance despite communication challenges.
Keywords: communication; Consensus algorithm; distributed control; microgrid; power quality